Outsourcing success : determining its critical managerial factors in services industry / Nilakshi W.K. Galahitiyawe - Galahitiyawe, Nilakshi W.K. (2013)
Outsourcing is gaining increasing importance as a form of business collaboration. Outsourcing in the services sector involves transferring total or partial ownership of performing the business activity(ies) to a vendor(s). To ensure the success of outsourcing, the integration of the tasks between the firm and the vendor must be well and efficiently managed. The purpose of this study is to identify the factors that need to be managed in the process of integration of outsourcing tasks. This study identified that managing organizational dependency and governance in the process of the exchange of resources are the most fundamental aspects of outsourcing success. Accordingly, managing organizational dependency is examined through the Resource Dependency Theory, while governance in the exchange of resources is viewed from the perspective of the Social Exchange Theory. Degree of outsourcing, vendor management capability and vendors‟ service performance are identified as factors that have a direct impact on outsourcing success in services. This study also tests the effects of the magnitude of the partners‟ compatibility and partnership quality in the collaborative business, on „outsourcing success‟. Cross-sectional data is collected through a survey of managers in the banking and hotel sectors in Sri Lanka using self-administered structured questionnaires. A total of 207 usable responses are collected. Structural Equation Modelling (SEM) is used to analyse the survey responses. The findings of this research confirmed that dependency and exchange are crucial aspects that need to be managed in services outsourcing, as they constitute 95 per cent of the success. The degree of outsourcing is determined by the level of breadth and level of depth, of which only the former significantly affects the success of outsourcing. The empirical evidence also verified that the influence of contractual governance on outsourcing success is higher when the partners‟ compatibility and/or partnership quality is higher. This research has contributed to the area of strategic service supply chain management. This study contributes to the body of knowledge as it provides validated measurement constructs for outsourcing success in the services sector. The present study adapted the INDSERV scale developed by Gounaris (2005a) to measure vendors‟ service performance, and it found that the scale should be localized in future research. In addition, the empirical verification of the moderating roles of partners‟ compatibility and partnership quality are the main contributions to the theory. The influence of partnership quality and partners‟ compatibility on contractual governance is different. This raises several managerial implications. Maintaining a higher level of partners‟ compatibility is more important than partnership quality for the focal firm as it minimizes the efforts of vendor management activities. In contrast, a higher level of partnership quality becomes more important than partners‟ compatibility for vendors as it enhances the impact of vendors‟ service performance on outsourcing success. As a whole, the identification of prominent managerial factors, which are related to outsourcing success, allow all the service industry stakeholders to plan, execute and assess the outsourcing function as a collaborative business practice that ensures the mutual benefits as well as mutual survival.